1986
DOI: 10.1097/00004032-198607000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Safety Aspects of Laser Scanning Ophthalmoscopes

Abstract: Safety standards such as American National Standards Institute Z-136.1 do not give clear light-level limitations for laser scanning ophthalmoscopes. To have more than a rough estimation the retinal temperature rise due to intraocular scanning laser illumination was calculated on the basis of a thermal model. The predicted temperature development with time was compared with the calculated effect of other retinal illumination patterns with well-known hazard risks. The similarity of the thermal effect of retinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1989
1989
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…Thus, a more appropriate evaluation of laser projection systems is possible, taking into account the vertical scan movement. Klingbeil [21] suggests a reduction in the MPE of 20 % . At the same time the third pulse criterion has to be analyzed in detail.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a more appropriate evaluation of laser projection systems is possible, taking into account the vertical scan movement. Klingbeil [21] suggests a reduction in the MPE of 20 % . At the same time the third pulse criterion has to be analyzed in detail.…”
Section: Resultsmentioning
confidence: 99%
“…Scanned laser beams are already used in the entertainment industry for light shows and audience scanning [10,31] , in ophthalmoscopes [21,25] and for retinal scanning displays [34,41] . In the case of entertainment systems, persons in the audience are always several meters away from the light source.…”
Section: Methods and Approaches To Determine Laser Classmentioning
confidence: 99%
“…The exposure levels of both lasers were lower than the standard maximum-permissible levels according to the American National Standards Institute and well within the safety range for a 1000-second continuous exposure time. 19 The laser beams were combined and relayed into a handheld module via an optical fiber. The hand-held module enclosed an X-Y scanning mirror system and optics that directed the scanned beam into the entrance pupil of the subject's eye.…”
Section: Methodsmentioning
confidence: 99%
“…Model cal culations for the temperature rise of the retina caused by laser scanning (Klingbeil, 1986) showed that the situation can be approximated by a repeatedly pulsed area illumination. However, the case of scanning illumination, which is a combination of continuous and pulsed exposure, is not considered by ANSI.…”
Section: B Light Levels and Safetymentioning
confidence: 99%